Caracterização de ß-galactosidases purificadas de caules de plântulas de Vigna unguiculata semeadas na ausência e na presença de NaCl - Sudério, Fabrício Bonfim (2007)
The (3-galactosidases a widespread family of enzymes involved in several biological processes in plants, including plant growth. These enzymes acts on hydrolyzes of lactose to galactose plus glucose but also acts as a transglycosylase, altering the structure of lactose [...]